Gut Hormones in T2 Diabetes Mellitus and Emerging Treatment Paradigm - S S Sreenivas (Medical Science: Trends and Innovations Vol. 10, 2025)
Diabetes mellitus (DM) is a chronic metabolic disease of major public health concern worldwide. DM prevalence is more alarming in low and middle-income countries than in high-income countries. DM characterized by insulin resistance (IR) or deficiency is either insulin-dependent (T1DM) or non-insulin-dependent (T2DM). Among the T2DM cases, 50% are not properly medicated due to poor knowledge and coverage of treatment. T2DM is a condition of insensitivity of pancreatic \(β\)-cells to glucose-stimulated insulin release and impairment of skeletal muscle cells to insulin-stimulated glucose entry, IR. Impaired regulation of incretin hormones which reduce BG levels is a fundamental defect in the pathogenesis of T2DM. The Gut-brain axis has a key role in the regulation of energy homeostasis and glucose metabolism through the action of various hormones. Gut hormones are peptides synthesized by specialized enteroendocrine cells located in the epithelium of the stomach, small bowel and large bowel. Gut hormones activate neural circuits to signal peripheral organs for coordination of overall energy intake and assimilation. Incretins, Leptin, CCK, Oxyntomodulin, PYY and Gastrin are the major gut hormones involved in glucose metabolism. A group of gut peptides that are secreted after nutrient intake and stimulate insulin secretion together with hyperglycemia are known as incretin hormones. Certain gut hormones like cholecystokinin (CCK) and gastrin are reported to activate pathways that promote islet neogenesis and improve glucose homeostasis in T2DM. Currently, DPP-4-resistant GLP-1 receptor agonists (incretin mimetics), and inhibitors of DPP-4 activity (incretin enhancers) are being successfully used clinically for the treatment of T2diabetes mellitus. Presently, hormonal synergy is of therapeutic interest for the treatment of diabetes mellitus. Gut hormones such as OXM, ghrelin and PYY play a crucial role in the regulation of glucose. Pleiotropic actions of leptin reported to lower glucose is also, an area of investigation for hyperglycemia. Studies have proved that these hormonal actions are a possible platform for therapeutic development in T2DM management. The study also concluded that bariatric surgery has given new thinking on exploiting hormonal changes to target future medical therapies for Type 2 diabetes mellitus. It may be possible to reset metabolism and reverse diabetes taking advantage of knowledge gained from bariatric surgery.